Table of Content - -, (Journal of Educational and Psychological Sciences, 2024)
Table of Content:1. Performance Development of Islamic School's Principals in Republic of India  in the light of educational CompetenciesMr. Badruddin Mohammad Saleem, Prof. Abdullah Mohammad Al-Manea2. The impact of the shortage of educational supervisors in the Jerusalem Education Directorate  on the quality of teachingMs. Dima Yousef Atoun, Dr. Ibrahim Arman3. The Role of School Principal's Strategic Vision in Achieving Organizational Excellence: An Analytical Study of Secondary SchoolsMs. Sondos Naif Ezzdeen Alulaime4. Patterns of administrative practices for secondary school principals in the southern governorates of PalestineDr. Heba Uqelan Abed Al-Aziz Elyan5. The reality of educational supervision in following up the educational process based on distance education in the city of Jeddah from the supervisors' point of viewMrs. Amal Ali Mofraq Al-Shehri, Dr. Rabab Al-Harbi6. Effect of the perspectives of intellectual disabilities teachers towards the absence of job security and its impact in day care centersMrs. Ebtisam Saeed Al-Sihli, Dr. Walaa Abdullah Khares7. Parent-child Relationship in the Digital EraMs. Suzan Muhammad Abu Hilal, Prof. Iyad Saleem El-Halaq
Keywords: Journal of Educational and Psychological Sciences